The High Rate of Judicial Divorce among Women of Lower Education in Madura-Indonesia: A Gender Perspective - Hannan, Abd; Syarif, Zainuddin (UIN Sunan Kudus, 2023)
This study examines the high rate of judicial divorce among women of low education in Madura This research is a field study using a qualitative method. The data originated from primary data based on observation and interviews, and secondary data in the form of statistics. Using analysis based on sociology of gender theories, specifically the Women and Development (WaD) and Talcott Parson’s structural feminism theory, this study obtained three findings. First, the dynamics of divorce in Madura increased in the last three years (2018-2020). By type, divorces in Madura are mostly judicial than repudiatory,. The second finding is that there are two categories of factors underlying the rise of judicial divorce. The first is direct factors such as the economy, abandonment, and domestic violence. The second category is indirect factors, such as low education level, while only 7% had higher education. From the perspective of Parson’s structural feminism theory, the study also found that the high number of women with low education levels involved in a judicial divorce in Madura negatively impacts their existence and experience. In numerous cases namely violence against women.